Matrix metalloproteinase gene expressions might be oxidative stress targets in gastric cancer cell lines - Gencer, Salih; Cebeci, Anil; Irmak-Yazicioglu, Meliha Burcu (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Objective: Oxidative stress is linked to increased risk of gastric cancer and matrix metalloproteinases (MMPs) are important in the invasion and metastasis of gastric cancer. We aimed to analyze the effect of the accumulation of oxidative stress in the gastric cancer MKN-45 and 23132/87 cells following hydrogen peroxide (H2O2) exposure on the expression patterns of MMP-1, MMP-3, MMP-7, MMP-9, MMP-10, MMP-11, MMP-12, MMP-14, MMP-15, MMP-17, MMP-23, MMP-28, and β-catenin genes. Methods: The mRNA transcripts in the cells were determined by RT-PCR. Following H2O2 exposure, oxidative stress in the viable cells was analyzed by 2',7'-dichlorofluorescein diacetate (DCFH-DA). Caffeic acid phenethyl ester (CAPE) was used to eliminate oxidative stress and the consequence of H2O2 exposure and its removal on the expressions of the genes were evaluated by quantitative real-time PCR. Results: The expressions of MMP-1, MMP-7, MMP-14, MMP-15, MMP-17 and β-catenin in MKN-45 cells and only the expression of MMP-15 in 23132/87 cells were increased. Removal of the oxidative stress resulted in decrease in the expressions of MMP genes of which the expressions were increased after H2O2 exposure. β-catenin, a transcription factor for many genes including MMPs, also displayed decreased levels of expression in both of the cell lines following CAPE treatment. Conclusions: Our data suggest that there is a remarkable link between the accumulation of oxidative stress and the increased expressions of MMP genes in the gastric cancer cells and MMPs should be considered as potential targets of therapy in gastric cancers due to its continuous exposure to oxidative stress.